PENGARUH SUPERVISI AKADEMIK, IKLIM SEKOLAH, DAN KEMAMPUAN TIK TERHADAP KOMPETENSI PEDAGOGIK GURU SMK NEGERI DI KABUPATEN BLORA - Wahyudi, Miftah Sri; Kusumaningsih, Widya; Soedjono, Soedjono (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of the research is to determine the influence of academic supervision, school climate, and ICT capabilities on the pedagogical competence of State Vocational School teachers in Blora Regency. This research uses a quantitative research approach and an ex post facto type of research. The total research sample was 173 teachers. The prerequisite tests for this research analysis include the normality test, linearity test, homogeneity test and multicollinearity test. Hypothesis testing uses simple regression tests and multiple regression tests. The research results are: (1) there is a significant influence of academic supervision on the pedagogical competence of State Vocational School teachers in Blora Regency which is expressed by the regression equation Y = 39.393 + 0.690X1 and the magnitude of the influence is 39.0%; (2) there is a significant influence of school climate on the pedagogical competence of State Vocational School teachers in Blora Regency which is expressed by the regression equation Y = 25.174 + 0.894X2 and the magnitude of the influence is 38.8%; (3) there is a significant influence of ICT ability on the pedagogical competence of State Vocational School teachers in Blora Regency which is expressed by the regression equation Y = 18.110 + 0.678X3 and the magnitude of the influence is 68.2%; and (4) there is an insignificant influence of academic supervision, school climate, and ICT skills on the pedagogical competence of State Vocational School teachers in Blora Regency which is expressed by the regression equation Y = 9.173 + 0.033X1 + 0.189X2 + 0.589X3 and the magnitude of the influence is 68.8%.